Community Pharmacists’ Attitudes, Preferences and Barriers toward Continuing Pharmaceutical Education: A Cross Sectional Study in Jordan - Saadeh, Alaa; Jarab, Anan S.; Jaradat, Roa’a; Al Daqqa, Raneem (Jordan Journal of Pharmaceutical Sciences, 2023)
Community pharmacists’ responsibilities are expanding to foster optimal patient-centered care, which dictates postgraduate continuous education to enhance their competency and ability to face job challenges. We employed a cross-sectional online questionnaire-based study to evaluate community pharmacists’ attitudes towards continuous education, their preferred modes of program delivery, factors they consider before joining a program, their preferred topics to learn about, and potential perceived barriers against continuous education. A total of 358 community pharmacists completed the questionnaire. The majority of them (86.9 %) were interested in continuous education. However, most pharmacists (70.1%) had never attended any continuous education activity before. The most preferred type of delivery was self-learning through the internet (44.2%). Program cost and location were the major factors considered before accepting any activity (96.9%, and 96.6%, respectively). Among diseases, infectious disease was the most interesting topic for community pharmacists (92.7%). Regarding pharmaceutical topics, they were mostly interested in learning pharmacology and pharmacotherapy (94.1%), whereas pregnant and nursing mothers was the most desired patient group to learn about (92.2%). Job constraints and lack of time were the most reported barriers (89.4% and 89.1%, respectively). Community pharmacists’ have positive attitudes towards continuous education. However, many obstacles restrain them from effective participation in it. We provided sufficient data for policy makers to consider in future planning for continuous education activities that meet the needs of today’s pharmacists to advance their practice.